Preconceito, discriminação : mito ou realidade no contexto educacional - Nascimento, Inácia Maria Rodrigues do (2011)
This work had as objective to search the meaning of race, ethnicity, prejudice and discrimination at the school context, taking into account the Law 10.639/2003. Two state schools in the city of Aracaju (SE, Brazil) had been analyzed, through a methodology with ethnographical basis, which one is focused on participant´s observation, for elaboration of a diary of field. Questionnaires had been also applied with opened questions, to prove the transcriptions made in the diary. To understand the meaning of race, ethnicity, prejudice and discrimination, a bibliographical survey was made with issues that could be useful for us in order to understand these meanings and how they are materialized at schools. We firstly pointed the study of the abolition of the slavery, passing by the racial democracy, the meaning of mestizage‟ and the primordial concepts of race, ethnicity, prejudice and discrimination. In this way, we can collate the gotten analyses, with the bibliographical background, to answer the raised questions: At school, is `race' seen related to the color of the skin and/or to the ethnic group students belong to? Are prejudice and discrimination that happen at schools related to the social class the status? We prove partially such hypotheses and we perceive that the reality of the school show us other tracks for the meaning of such concepts.